2022
DOI: 10.3390/rs14051065
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Variations in Water Use Efficiency and Linkages with Land-Use Changes Using Three Different Data Sources: A Case Study of the Yellow River, China

Abstract: The dependence of water use efficiency (WUE) on changes in land cover types is crucial for understanding of long-term water availability and assessment of water-saving strategies. Investigating the impact of land cover types on ecosystem WUE has important implications when revealing water dynamics and land management. However, the determination of WUE and its dominant factors have always been subject to high data dependency and large calculation consumption within large basins. This paper proposes a framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This study investigated the impact of latitude, elevation, SM, and four meteorological variables (PRE, TEM, PDSI, and VPD) on WUE. It is worth noting that WUE can also be influenced by additional factors, such as rising atmospheric CO 2 (Battipaglia et al., 2020; Law, 2013; N. Liu et al., 2020; X. Liu et al., 2020), nitrogen deposition (Adams et al., 2021; Gharun et al., 2021; Law, 2013; X. Lu et al., 2019), solar radiation (H. Zheng et al., 2019; P. F. Zheng et al., 2019), nutrient cycling (Ding et al., 2022; Keenan et al., 2013; Morecroft et al., 1992), and change in land use (Guo et al., 2019; H. Sun et al., 2022). Previous research has demonstrated that CO 2 concentration can affect WUE by influencing plant physiology and stomatal conductance (L. He et al., 2017; X. Liang et al., 2023; Umair et al., 2020; Zhu et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the impact of latitude, elevation, SM, and four meteorological variables (PRE, TEM, PDSI, and VPD) on WUE. It is worth noting that WUE can also be influenced by additional factors, such as rising atmospheric CO 2 (Battipaglia et al., 2020; Law, 2013; N. Liu et al., 2020; X. Liu et al., 2020), nitrogen deposition (Adams et al., 2021; Gharun et al., 2021; Law, 2013; X. Lu et al., 2019), solar radiation (H. Zheng et al., 2019; P. F. Zheng et al., 2019), nutrient cycling (Ding et al., 2022; Keenan et al., 2013; Morecroft et al., 1992), and change in land use (Guo et al., 2019; H. Sun et al., 2022). Previous research has demonstrated that CO 2 concentration can affect WUE by influencing plant physiology and stomatal conductance (L. He et al., 2017; X. Liang et al., 2023; Umair et al., 2020; Zhu et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the role of precipitation extremes in shaping flood risk depends on land cover, region, and environmental conditions (Wang et al, 2017;Sun et al, 2022). Benito et al (2015) used the flood risk assessment model established by the ancient flood data to assess the risk in Europe.…”
Section: Introductionmentioning
confidence: 99%